Perancangan Knowledge Management System Pengelolaan Proyek di CV. Metric Design - Tanzil Ganefi, Robi; Hadiana, Ana; Pangaribuan, Imelda (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2016)
Increasing demand for development of mobile software and websites in 2011-2012 sue CV. Metric Design to use contract employees. But the using of contract employee services are causing the problem of knowledge loss when the contract is completed as a result transfer of the project from the employee to the employee replacement requires substantial time. In addition to the problems of knowledge management, the company is also the difficulty in monitoring the management of the project. Project managers find it difficult to monitor the achievement of tasks for each member of the project team. Blueprint of Knowledge Management Systems (KMS) is designed to integrate the knowledge management with project management development software. The design blueprint KMS made with reference to the 10-Step Knowledge Management Roadmap. The 10-step of this study limit up to the sixth stage which is making blueprint. KMS research results in the form of a blueprint comes with the implementation of the roadmap both infrastructure and human resources required in order to provide an overview for the company in implementing KMS. In order to enhance the research are advised to proceed to the last step of the 10-Step Knowledge Management Roadmap resulting KMS ready for use by the company.Â